POTENSI BATUGAMPING TERUMBU GORONTALO SEBAGAI BAHAN GALIAN INDUSTRI BERDASARKAN ANALISIS GEOKIMIA XRF - Aang Panji Permana (Universitas Lambung Mangkurat, 2018)
The potential of reef limestone in Gorontalo Province is very large. The proof is in two research stations in Kelurhan Buli'ide and Tanjung Kramat Village. Research on the potential of reef limestone using two methods of analysis petrology and geochemistry of XRF. Based on the results of the research both stations have the name of the rock and the composition of the chemical compounds is different. The results of the study differ from previous studies. Differences are found in the composition of CaO compounds higher than 80%. The chemical composition of compounds in two research stations has the potential to be developed into industrial material. Use of reef limestone can be used as building stones, road stabilizers, agricultural lime, ceramic materials, water purification and the process of deposition of non-ferrous metal ores.